2013
DOI: 10.1037/a0032121
|View full text |Cite
|
Sign up to set email alerts
|

Reversed item bias: An integrative model.

Abstract: In the recent methodological literature, various models have been proposed to account for the phenomenon that reversed items (defined as items for which respondents' scores have to be recoded in order to make the direction of keying consistent across all items) tend to lead to problematic responses. In this paper we propose an integrative conceptualization of three important sources of reversed item method bias (acquiescence, careless responding, and confirmation bias) and specify a multi-sample confirmatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
212
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(218 citation statements)
references
References 51 publications
1
212
0
5
Order By: Relevance
“…This is a dummy question to check the consistency of the respondents' attitude in answering the questions. 7,8) Therefore, we decided not to include the results of this particular question in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This is a dummy question to check the consistency of the respondents' attitude in answering the questions. 7,8) Therefore, we decided not to include the results of this particular question in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the poor fit of the reversely coded items may be attributed to acquiescence bias on survey responses (Weijters, Baumgartner, & Schillewaert, 2013). As acquiescence bias may be greater among cultures valuing interpersonal harmony and conformity (Johnson, Kulesa, Cho, & Shavitt, 2005), future research should seek to refine parent-reported measures of impulsivity within ethnic minority populations.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…The use of both positively and negatively worded items is common in questionnaires, to be able to reduce response bias . Known inconsistencies in responses between positively and negatively worded items are related to acquiescence (a tendency to agree with a statement), carelessness in responding (defined by Weijters et al as when the respondent is inattentive to reverse keyed items), and confirmation bias. The latter of these means that the respondent activates beliefs that are consistent with the items answered; for example, if they are asked whether they have trouble breathing right now, they will think of situations when this has occurred .…”
Section: Discussionmentioning
confidence: 99%
“…Known inconsistencies in responses between positively and negatively worded items are related to acquiescence (a tendency to agree with a statement), carelessness in responding (defined by Weijters et al as when the respondent is inattentive to reverse keyed items), and confirmation bias. The latter of these means that the respondent activates beliefs that are consistent with the items answered; for example, if they are asked whether they have trouble breathing right now, they will think of situations when this has occurred . One study investigated the advantages and disadvantages of instruments including combinations of positive and negative items versus those including only positive items.…”
Section: Discussionmentioning
confidence: 99%